Genetic diversity parameters in the natural populations of Calocedrus macrolepis in Tay Nguyen, Vietnam using ISSR markers - Lieu, Tran Thi; Quynh, Le Thi; Thu Hien, Vu Thi; Phong, Dinh Thi (Academia Journal of Biology, 2015)
Calocedrus macrolepis is one of 15 of coniferous species in the Central Highlands. This species has a wide distribution area with a large number of individuals, however, the species has recently been exploited for timber and pulp flavor, moreover, the habitat of species is being reduced. Without timely conservation measures this species will be at a high risk of extinction. In this paper, 30 ISSR markers were used to analyze the genetic diversity of species collected in Datanla (Lam Dong province), Hoa Son (Dac Lac province) and Kon Chu Rang (Gia Lai province) in the Central Highlands, Vietnam. Result of the analys is showed 25/30 markers polymorphic. A total of 129 DNA fragments were amplified, in which 65 fragments were polymorphic (50.39%). Genetic diversity was the highest in Datanla population of (I = 0.192, h = 0.102, PPB = 35.66%, Ne = 1.227 and He = 0.130) and the lowest in Kon Chu Rang population (I = 0.022, h = 0.015, PPB = 3.88%, Ne = 1.027 and He = 0.015). Analysis of molecular variance (AMOVA) results showed that the total level of molecular changes between populations was 36.33% and between individuals in the same population was 63.67%. A dendrogram constructed based on similarity matrix of 70 samples C. macrolepis divided into two main groups with genetic similarity coefficients ranged from 81.4% (Cm16 and Cm57) to 99.1% (Cm62 and Cm65) Molecular analysis results showed that C. macrolepis species should be protected at the population level.